Uncertainty, interest, gambling and conventional insurance - Htay, Sheila Nu Nu; Syed, Ahmed Salman (2013)
This paper acknowledges the needs of insurance in our daily life. The involvement of unfair elements in insurance brings the unjust contracts between the insurance companies and the insured. This paper takes social-economic justice approach to examine the unfair nature of insurance. It is highlighted that insurance involves uncertainty, interest and gambling. These are the main prohibited elements from Islam and these elements make insurance prohibited from the Islamic aspect.